Knowledge regarding risk factor and prevention strategies of osteoporosis among hospital attendants in Hospital Universiti Sains Malaysia - Ismail, Nor Afida (Universiti Sains Malaysia, 2015)
Osteoporosis is a worldwide health concern for individuals of both male and female which increases significantly with age without symptoms. The aim of this study was to determine the knowledge of risk factor and prevention strategies of osteoporosis among hospital attendant in Hospital Universiti Sains Malaysia (Hospital USM). A cross sectional study was used a self- administered questionnaire. A total of one hundred and one participants were involved in this study by using non-probability sampling. Data were collected from December 2014 to February 2015 using assessment tools and analysed using SPSS version 20.0 for frequency percentage, mean ,standard deviation and p-value .Results of 96(95%) showed that participants had higher knowledge score regarding risk factor of osteoporosis (M=1.95,SD=0.22). Meanwhile similar with the prevention strategies that reported had higher prevention strategies which was 61(60.4%), (M=1.60, SD=0.49).This study found that there is a significant difference between knowledge of risk factors among male and female (p =0.005) meanwhile for knowledge regarding prevention strategies showed that there were no significant (p =0.757) differences between male and female. More than that, there was no relationship between risk factor and prevention strategies of osteoporosis among participants. Thus, intervention regarding risk factor and prevention strategies should be identified as well as other intervention to prevent from the other complication in the future.